Line-to-Line Reaming of Highly Porous Acetabular Components Improves Position and Reduces Variability of Component Placement - Bedair, Hany; Antioch, Valentin; Heaven, Sebastian (The Journal of Hip Surgery, 2017)
Accurate and precise acetabular component position in total hip arthroplasty remains challenging even for experienced, high-volume surgeons. Some variability may result from the press-fit technique of cementless components and maybe magnified by the use of highly porous cups with high-friction surfaces. The purpose of this study is to investigate the acetabular component positioning of a hemispherical, highly porous cup with line-to-line reaming compared with press-fit techniques. A retrospective cohort study was performed of 110 consecutive primary total hip arthroplasties performed by a single surgeon using a highly porous acetabular component. Half of the patients had the component implanted with a line-to-line reaming technique and the other half were implanted using a 1 mm press-fit technique. Postoperative radiographs were evaluated for component positioning and loosening at a minimum of 1 year postoperatively by two independent surgeons. Records were reviewed for subsequent surgery. There were no differences between the groups with respect to age, sex, body mass index, operative side, or acetabular component size. The press-fit group had an average abduction angle of 49.4 ± 5° and anteversion of 20.6 ± 7°. The line-to-line group had an average abduction angle of 45.02° [standard deviation (SD) 4.58] and anteversion of 25.42° (SD 4.44) and were statistically different from the press-fit group (p < 0.01). There was significantly less variability in the line-to-line group with respect to anteversion (F-test, p < 0.01) compared with the press-fit group. At most recent follow-up, there were no dislocations, revisions for any reason, or radiographic evidence of loosening in either group. Line-to-line reaming for highly porous cups can improve component positioning and reduce variability compared with press-fit techniques with no difference in fixation or other clinical outcome parameters.
Keywords: hip; arthroplasty; acetabular component; component positioning